Original articleDifferential expression of microRNA-210 in gliomas of variable cell origin and correlation between increased expression levels and disease progression in astrocytic tumours - Lai, Niansheng; Zhu, Hao; Chen, Yijun; Zhang, Shuai; Zhao, Xudong; Lin, Yuchang (Folia Neuropathologica, 2014)
Introduction: The microRNA, miR-210, is frequently associated with hypoxia induction, and an increase in its levels is often correlated with poor prognosis in many solid tumours. The present study examines the levels of miR-210 in glioma tumours of multiple origins to determine if an association can be established with disease progression. Material and methods : Tissue samples were acquired from normal brain tissue, oligodendroglial tumours and astrocytic tumours. The astrocytic tumours were further divided by grade: diffuse astrocytomas (WHO grade II), anaplastic astrocytomas (WHO grade III), and glioblastoma (WHO grade IV). The expression of miR-210 was examined by real-time quantitative RT-PCR. The correlation of the expression of miR-210 and astrocytic tumour grade was analyzed by the Spearman correlation test. Results : MiR-210 presents a differential expression depending on the origin of the glioma. Oligodendroglial tumours exhibit a significantly reduced level of miR-210 as compared with normal brain tissue. In contrast, astrocytic tumours demonstrate significantly increased levels of miR-210. Furthermore, the expression of miR-210 is positively correlated with the grade of astrocytic tumour, in the following order: grade IV > grade III > grade II > normal brain tissue (p < 0.05). Conclusions : MiR-210 levels can be potentially established as a biomarker for pathological diagnosis of malignant astrocytic tumour progression. In addition, the expression of miR-210 can be utilized as an additional identification measure of glioma tumour origin.